Menopause and exercise: hormonal influences on cardiovascular regulation: a narrative review - Głuski, Jacek; Borowiecka, Patrycja Anna; Brzozowska, Agnieszka; Radziwonka, Agnieszka; Garbacz, Anna Izabela; Majszyk, Tomasz Julian; Węglarz, Aleksandra Karolina; Kosiorek, Paweł; Niezgoda, Ada; Olborska, Anna; et al. (Quality in Sport, 2026)
The menopausal transition is associated with hormonal changes that adversely affect cardiovascular regulation and contribute to increased cardiovascular disease risk in women. Declining estrogen availability is linked to alterations in vascular function, blood pressure regulation, autonomic balance, and metabolic health that extend beyond the effects of chronological aging alone. This narrative review summarizes current evidence on menopause-related cardiovascular changes and examines the effects of physical activity and structured exercise training on vascular, hemodynamic, autonomic, and cardiorespiratory outcomes in peri- and postmenopausal women. Available evidence indicates that menopause is associated with increased arterial stiffness, altered blood pressure regulation, and a shift toward sympathetic predominance. Exercise training, particularly aerobic exercise, is consistently associated with improvements in arterial function, blood pressure control, cardiorespiratory fitness, and autonomic regulation. Resistance-based training shows more variable cardiovascular effects but supports broader functional and metabolic adaptations. Notably, many exercise-related benefits occur independently of significant weight loss, underscoring the importance of physiological rather than purely anthropometric mechanisms. Overall, regular exercise emerges as an effective systems-level strategy for attenuating menopause-related cardiovascular dysregulation and supporting cardiovascular health during and after the menopausal transition.